Complete Git Guide Understand and Master Git and GitHub - Stashchuk, Bogdan (Packt Publishing, 2020)
Master basic to advanced Git features such as commits, branches, merging, rebasing, and squashing. About This Video Learn all basic and advanced Git features Practice managing repositories with GitHub, SourceTree, and VisualStudio Code Understand how Git and GitHub work under the hood In Detail Complete with practical activities, this comprehensive Git and GitHub guide will help you understand how Git works. You'll learn how to use Git features efficiently and fix issues in your development workflow. Starting with the internal structure of a Git repository, this course will take you through the four types of Git objects: blobs, trees, commits, and annotated tags. You'll understand how each object has a unique SHA-1 hash and how all objects are stored in folders, files are stored in blobs, and filenames are stored in other Git objects called trees. You'll even get to grips with creating new Git objects without using git commit and git add. Once you've created Git objects in the Git repository, you will add it to the staging area and working directory. By the end of this course, you'll have become a Git and GitHub expert and be able to perform basic and advanced Git tasks seamlessly.